Performance evaluation of PV-Trombe wall for sustainable building development - Irshad, K. (Elsevier B.V., 2015)
This paper presents, a detailed simulation model of a single room building integrated with PV Trombe wall (PV-TW). Performance is evaluated in terms of room temperature, cooling load and PV efficiency by varying the air flow velocity for three different PV-TW Glazing types (i.e. Single Glazing, Double glazing, Double glazing filled with gas (Argon)). Simulation was done on TRNSYS software having inputs parameter as climatic conditions, building construction details, thermal properties of materials, detail of PV-TW and orientation of the building were inserted. By varying the air flow velocity and comparing the results of all three types of glazing it was found that PV Double glazing filled with argon shows significant results in reduction of cooling load of building, mean air duct temperature. Reduction of mean air duct temperature results in lowering of PV cell temperature which enhances the efficiency of PV panel. Also maximum room temperature reduction was found while using a double glass filled with argon PV-TW, which further reduces thermal load of the building. Air flow velocity shows significant effect on the performance of PV-TW up to certain values after which its effect stagnates and no further improvement was shown in all three types of PV-TW. Â© 2015 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.